Chiral Synthesis of Carbocyclic Nucleoside Analogs from Noncarbohydrate Precursors - Fabio Casu; Maria Assunta Chiacchio; Roberto Romeo; Giuseppe Gumina (Current Organic Chemistry, 2007)
Nucleosides represent a very important group of molecules, both chemically and biologically. Over the past forty years, the continued success of nucleoside analogs as chemotherapeutic agents has been both the result of and the driving force for the development of new synthetic methodologies to access analogs that may differ considerably from natural nucleosides. Among the many classes of nucleoside analogs that have been prepared and evaluated, carbocyclic nucleosides featured diverse and challenging syntheses and interesting biological activity. Carbohydrate chemistry has been elegantly and thoroughly exploited for the synthesis of carbocyclic nucleoside analogs, thanks to the availability and versatility of highly functionalized chiral precursors. In a number of examples, however, the synthesis of carbocyclic nucleosides has been elegantly and efficiently achieved from non-carbohydrate starting materials, either from natural optically active molecules, via chemical or enzymatic desymmetrization of prochiral molecules, or resolution of racemates. This review will discuss chiral syntheses of carbocyclic nucleoside analogs from non-carbohydrate precursors.
Keywords: cyclopentyl nucleosides